THE USE OF TIKTOK AND SNACK VIDEO APPLICATIONS AGAINST STUDENT INCOME BASED ON JU'ALAH AKAD (Case Study Of Students Of The Faculty Of Economics And Business, Malikussaleh University) - Nazli Hasan; Fuadi; Falahuddin; Arliansyah; Santriani Br Bancin (PT. Radja Intercontinental Publishing, 2023)
This study examines the practice of using the TikTok application and video snacks for Malikussaleh University Faculty of Economics and Business students in generating income based on the Ju'alah contract. The population in this study are all active students of the Faculty of Economics and Business, Malikussaleh University from 2015-2022, with a total of 3,450 students, including 872 students (S1), 2,578 students (S1) with a sample size of 10 (Ten) respondents consisting of 6 (Six) users of the tiktok application and 4 (Four) users of the video snack application. With the research method in the form of a qualitative analysis method by conducting direct interviews with respondents to get answers to the problems studied. The results showed that there is a practice of using the TikTok and Snack Video applications in obtaining income for students of the Faculty of Economics and Business, Malikussaleh University which is in accordance with the provisions of the Ju'alah contract. where in this Tiktok and Snack Video application there are Ja